Analisa Pengujian Produk Solar Cell Berbasis Standar Nasional Indonesia (SNI) - Alimuddin Alimuddin; Alifia Mariatul Qibtiah; Rocky Alfanz; Ria Arafiyah; Muhammad Iman Santoso (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2023)
Abstract The research objective is to understand the testing stages of the Indonesian national standardization process on local solar cell products circulating and installed in Indonesia, both imported and local. The solar module is the main component of a solar power plant which has a very important role for its function as a converter of solar energy (the sun) into electrical energy. Solar modules in Indonesia have special standards set by the Indonesian Standardization Agency (BSN). The solar power plant itself is one of the new renewable energy sources (EBT) that produces electricity from the stages of the photovoltaic effect system. Solar power plants can be utilized by people who need electrical energy, but are constrained by the unavailability of electrical energy from PLN, such as people in 3T areas (outermost, underdeveloped, remote) that have not received electricity from PLN.Keywords: Indonesian National Standardization, Solar Module, Solar Cell